2007
DOI: 10.1002/jso.20741
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the RT‐PCR positive sentinel node in melanoma

Abstract: Sentinel node RT-PCR positivity did not risk stratify histologically negative melanoma patients beyond routine pathologic examination in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Along with histopathological analysis, many centers also perform studies using other techniques such as RT‐PCR, for the molecular detection of melanocytic markers, and immunocytology for the detection of melanoma cells [44, 46, 47]. In these techniques, the sentinel lymph node is cut in half, i.e., histopathological analysis is performed on half a node.…”
Section: Resultsmentioning
confidence: 99%
“…Along with histopathological analysis, many centers also perform studies using other techniques such as RT‐PCR, for the molecular detection of melanocytic markers, and immunocytology for the detection of melanoma cells [44, 46, 47]. In these techniques, the sentinel lymph node is cut in half, i.e., histopathological analysis is performed on half a node.…”
Section: Resultsmentioning
confidence: 99%
“…The prognostic significance of PCR analysis of melanocyte‐associated markers in melanoma SLNs is controversial (4–12, 17–25). However, a recently published meta‐analysis has concluded that PCR status of the SLNs appears to have a clinically valuable prognostic power in patients with melanoma (26).…”
Section: Discussionmentioning
confidence: 99%
“…Since these molecular techniques examine all the tissue submitted, they may be more sensitive than standard histopathological methods for detecting metastases. Indeed, a number of PCR‐based studies have shown significantly higher positivity rates for melanoma SLNs compared with traditional methods of analysis, with up to 70% of nodes positive for melanocyte markers (3–12). However, these molecular detection rates are also much higher than would be expected if PCR detects metastases alone, since the natural history of melanoma suggests that only up to 30% of stage I and stage II melanoma patients are likely to develop lymph node metastases (13).…”
mentioning
confidence: 99%
“…The retrotranscription reaction was performed with 2 mg of RNA that was isolated using TRIZOL reagent Primers for tyrosinase were TYR-F: TTG GCA GAT TGT CTG TAG CC; TYR-R: AGG CAT TGT GCA TGC TGC TT; 284 bp, 35 cycles of 1 min at 951C; 1 min at 551C; 1 min at 721C [16][17][18]. Water instead of cDNA and MCF-7 cell line was used as negative controls.…”
Section: Reverse-transcription-pcrmentioning
confidence: 99%